Decoding early and late cortical contributions to individuation of attended and unattended objects. (February 2018) - Naughtin, Claire K.; Mattingley, Jason B.; Bender, Angela D.; Dux, Paul E.
Abstract: To isolate a visual stimulus as a unique object with a specific spatial location and time of occurrence, it is necessary to first register ( individuate ) the stimulus as a distinct perceptual entity. Recent investigations into the neural substrates of object individuation have suggested it is subserved by a distributed neural network, but previous manipulations of individuation load have introduced extraneous visual confounds, which might have yielded ambiguous findings, particularly in early cortical areas. Furthermore, while it has been assumed that selective attention is required for object individuation, there is no definitive evidence on the brain regions recruited for attended and ignored objects. Here we addressed these issues by combining functional magnetic resonance imaging (fMRI) with a novel object-enumeration paradigm in which to-be-individuated objects were defined by illusory contours, such that the physical elements of the display remained constant across individuation conditions. Multi-voxel pattern analyses revealed that attended objects modulated patterns of activity in early visual cortex, as well as frontal and parietal brain areas, as a function of object-individuation load. These findings suggest that object individuation recruits both early and later cortical areas, consistent with theoretical accounts proposing that this operation acts at the junction of feed-forward and feedback processing stages in visual analysis. We also found dissociations between brain regions involved in individuation of attended and unattended objects, suggesting that voluntary spatial attention influences the brain regions recruited for this process. Highlights: We reveal novel insights into the distributed neural substrates of object individuation. We combined fMRI with a novel illusory-contour enumeration paradigm. This paradigm manipulated individuation load while controlling for low-level visual factors. We find evidence of object individuation in activity throughout the brain. Object individuation is influenced by selective attention mechanisms.